2007
DOI: 10.1136/ard.2006.067124
|View full text |Cite
|
Sign up to set email alerts
|

B cell depletion therapy in systemic lupus erythematosus: long-term follow-up and predictors of response

Abstract: Objectives: To describe the long-term clinical outcome and safety profile of B cell depletion therapy (BCDT) in patients with systemic lupus erythematosus (SLE). It was also determined whether baseline parameters can predict the likelihood of disease flare. Methods: 32 patients with refractory SLE were treated with BCDT using a combination protocol (rituximab and cyclo-phosphamide). Patients were assessed with the British Isles Lupus Assessment Group (BILAG) activity index, and baseline serology was measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 10 publications
2
108
0
14
Order By: Relevance
“…In 15 of 40 patients (38%), anti‐dsDNA levels normalized, with the majority (13 of 15) having had levels ≤1,000 IU/ml at baseline (Figure 5D). No serious adverse events were observed 31, 33, and none of the patients required intravenous Ig therapy.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In 15 of 40 patients (38%), anti‐dsDNA levels normalized, with the majority (13 of 15) having had levels ≤1,000 IU/ml at baseline (Figure 5D). No serious adverse events were observed 31, 33, and none of the patients required intravenous Ig therapy.…”
Section: Resultsmentioning
confidence: 91%
“…A typical rituximab treatment cycle consisted of rituximab, 2 doses of 1 gm given 1–2 weeks apart in combination with 1 dose of intravenous cyclophosphamide (750 mg). The clinical response to rituximab in this cohort has been reported previously 31. Clinical and laboratory parameters were analyzed during the first cycle of rituximab (up to 12 months) and the most recent time point from all patients, some of whom had received multiple cycles of rituximab‐based treatment in combination with concomitant and/or subsequent therapy with immunosuppressants to determine longer‐term effects on the recovery of B cell subpopulations, serum Ig, and autoantibodies.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Rituximab was first introduced in clinical prac-tice for the treatment of non-Hodgkin's lymphoma and then extended to autoimmune diseases (12), such as rheumatoid arthritis (13), lupus erythematosus (14,15), vasculitic disorders (16), and membranous nephropathy (12,17,18). Recent uncontrolled studies suggest that RTX may maintain remission of INS as effectively as standard therapy based on prednisone and calcineurin inhibitors (19 -22).…”
Section: Introductionmentioning
confidence: 99%
“…9 -11 More than 20 studies of almost 300 patients reported response rates averaging 75% in refractory lupus or lupus nephritis treated with rituximab (Table 1). [12][13][14][15][16] Responses are accompanied by falls in anti-double-stranded DNA antibodies, correction of complement depletion, and reduction in glucocorticoid requirement. Varying treatment protocols, response criteria, and positive reporting bias indicate caution is necessary in interpreting these results, compounded by the failure of the first randomized trial, EXPLORER (A Study to Evaluate the Efficacy and Safety of Rituximab in Patients With Severe Systemic Lupus Erythematosus), to demonstrate a superior response to rituximab in addition to glucocorticoids for remission induction in nonrenal lupus.…”
mentioning
confidence: 99%